2003
DOI: 10.1109/tnb.2003.820268
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast attachment to a textured surface in the absence of exogenous adhesion proteins

Abstract: The present study investigated whether osteoblasts could attach to a culture substratum through a surface texture-dependent mechanism. Four test groups were used: (A) untextured, and three texture groups with maximum feature sizes of (B) <0.5 microm, (C) 2 microm, and (D) 4 microm, respectively. All surfaces were coated with the nonadhesive protein bovine serum albumin (BSA). Osteoblasts were allowed to adhere in serum-free medium for either 1 or 4 h, at which time nonadherent cells were removed. At 4 h, untex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Albumin binds with lipids, regulates cytoplasmic calcium oscillations, and stimulates proliferation of osteoblasts 39) . Albumin also enhances fibronectin-integrin interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin binds with lipids, regulates cytoplasmic calcium oscillations, and stimulates proliferation of osteoblasts 39) . Albumin also enhances fibronectin-integrin interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Stem/ osteoprogenitor cells attach to the implant surface via interaction of cell integrins with adsorbed proteins, the extent of which may consequently affect the spread, proliferation, and differentiation of cells. [23][24][25][26] Osteoblast attachment on titanium surfaces in the presence of preadsorbed proteins was observed to be enhanced compared with osteoblast attachment on control titanium surfaces without preadsorbed proteins. 27 However, ANs@TiNWs with high protein adsorption showed low MG63 cell adhesive capacity in our study, which may be due to the special nanostructure of the ANs@ TiNWs, with their larger specific surface area favoring protein adsorption but limited binding sites available for adhesion of MG63 cells.…”
Section: Notesmentioning
confidence: 93%
“…show normal growth and proliferation on CNTs [116][117][118][119]. Figure 2.25 shows fibroblast cells grown on vertically aligned carbon nanotubes [116].…”
Section: Biocompatibility Of Ha-cnt Compositesmentioning
confidence: 99%
“…Figure 2.25 shows fibroblast cells grown on vertically aligned carbon nanotubes [116]. Recent studies have reported increased proliferation and adhesion of osteoblast cells on CNT surface, due to the selective absorption of proteins on the CNT surface from cell culture medium [120][121].…”
Section: Biocompatibility Of Ha-cnt Compositesmentioning
confidence: 99%
See 1 more Smart Citation